The Influence of Self-Efficacy, Work Discipline and Organizational Culture On Employee Performance Mediated By Job Satisfaction - Iman Saro, Pieter; Heryjanto, Andreas (Pelopor Publikasi Akademika, 2024)
The study aimed to examine self-efficacy, work discipline and organizational culture on employee performance mediated by job satisfaction. In this study, the technique of taking data sources by means of non-probability sampling with purposive sampling method. The sample used was employees at PT APM Logistics collected through a google form online questionnaire totaling 145 respondents. This study uses Partial Least Square SEM or what is called PLS-SEM. This study uses variables of self-efficacy, discipline and culture as dependent variables, employee performance as an independent variable, and job satisfaction as a mediating variable. The results of this study indicate that efficacy has no positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, self-efficacy has a positive and significant effect on job satisfaction, work discipline has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, job satisfaction mediates the effect of self-efficacy on employee performance, job satisfaction mediates the effect of work discipline on employee performance, job satisfaction does not mediate the effect of organizational culture on employee performance